The electrical properties of Au/GaN and PEDOT: PSS/GaN diodes - Ali Sadoun; Imad Kemerchou; S. Mansouri; M. Chellali (International Journal of Energetica)
In the present paper, using a numerical simulator, the simulation of Au/n-GaN and PEDOT: PSS/GaN structures were performed in a temperature at room temperature. The electrical parameters: barrier height, ideality factor, shunt resistance series, and resistance have been calculated using different methods: conventional I-V, Norde, Chattopadhyay, and Mikhelashvili. Statistical analysis showed that the Au/GaN structure has a barrier height of (0.6 eV) which is higher compared with the PEDOT: PSS/GaN structure (0.72 eV) and ideality factor (1.88 and 2.26) respectively. The values of resistance shunt were increased from 77150.056 Ω to 11207586 Ω. It is observed that the leakage current increased from 6.64E-5 to 4.98926E-5A at −0.85 V.